Dinamika Islam Tradisional di Kalimantan Timur: Implikasinya Terhadap Pendidikan Nilai dalam Masyarakat Multikurtural - Fansuri, Fuad; Susmiyati, Sri; Elmi, Akhmad Rijali; Rahmat, Abdur (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2022)
Islam is a universal religion with the ability to persist and adapt to changing contexts of space and time. The diversity of religious practices observed by communities in various regions further emphasizes the pluralistic religious culture in Indonesia. One such region with distinct religious traditions is East Kalimantan. This study aims to describe the religious practices of the Muslim community in East Kalimantan and analyze Islam's perspective on these traditions. Various religious traditions still preserved as a form of cultural heritage include birth ceremonies, the commemoration of the Prophet's birthday (Maulid Nabi), wedding rituals, expressions of praise for the Prophet through Hadrah, and rituals associated with death. Studies on these religious traditions show that Islam possesses a perfect, comprehensive, and flexible nature. As a complete religion, Islam not only encompasses the teachings given to the prophets and previous communities but also provides comprehensive guidelines relevant to various aspects of human life across different contexts of space and time.